Identification and assessment of antimicrobial resistance bacteria in a hemodialysis water treatment system. (3rd February 2022) - Chaoui, Laila; Chouati, Taha; Zalegh, Imane; Mhand, Rajaa Ait; Mellouki, Fouad; Rhallabi, Naima
Abstract: The water treatment process is a vital factor for hemodialysis (HD) patients. This study aimed to assess the degree of contamination of HD water by bacteria at the HD center of Mohammedia, Morocco, in addition to evaluating the antimicrobial resistance of isolated bacteria. Fifty-four water samples were taken, the appropriate cultures were used to isolate the pathogenic bacteria, which were identified biochemically and molecularly by 16S RNA sequencing. Their susceptibility to antimicrobial drugs was determined by the disk diffusion method. Approximately 5.5% of water samples were above the norm. The isolated bacteria that colonized the HD systems were mostly Gram-negative bacilli, such as Stenotrophomonas maltophilia, Pseudomonas spp., and Burkholderia cepacian . Results of the antibiotics test showed remarkable resistance levels. Among Pseudomonas spp. and S. maltophilia, 10 strains were classified as multidrug-resistant (MDR), and 4 as extensively drug-resistant (XDR). The diversity of bacterial strains isolated in the water used for HD treatments, and their worrying resistance levels pose a significant risk to patients. For these reasons, an urgent need for periodic microbiological monitoring of water after each treatment step must be applied, and the treatment process should also be optimized. HIGHLIGHTS: Overall, the water quality in the Mohammedia HD center does comply with the minimum requirement of hemodialysis water. Bacteria with pathogenic potential in hemodialysis water. Bacteria with high antimicrobial resistance.